PERANCANGAN IDENTITAS VISUAL UNTUK USAHA PETERNAKAN BABI "PADABA IRVAN" - Tefa , Ariance (Jurnal Industri Kreatif dan Inovatif, 2025)
This study discusses the design of a visual identity, particularly a logo, for the pig farming business "PADABA IRVAN", owned by Mr. Epi Selan and his family, located in Soe, East Nusa Tenggara, Indonesia. The business has been running since the 1980s and is known for its 24-hour meat ordering service. The main goal of this design is to create a strong visual identity that builds brand recognition, attracts customers, and expands market reach. The design process involved data collection through interviews and direct observation, followed by analysis using Roland Barthes’ semiotic theory, which includes denotation, connotation, myth, and symbolic codes. The logo incorporates elements such as a pig’s head, fresh meat, a knife, a 24-hour clock symbol, and the brand name—all of which visually communicate the business’s values and uniqueness. The result shows that a strong visual identity serves not only as a recognizable symbol but also as a communication tool that effectively conveys the brand’s message to the public. The visual identity of "PADABA IRVAN" is expected to support business growth and strengthen customer trust.